Ecological restoration effects of the Beijing–Tianjin Sandstorm Source Control Project in China since 2000. (February 2023) - Li, Changlong; Gao, Zhihai; Sun, Bin; Wu, Junjun; Wang, Hongyan; Ding, Xiangyuan
Graphical abstract: Highlights: A vegetation–water–soil–environment ecological restoration evaluation system. Optimized models were used to evaluate the four-dimensional ecological functions. The 4D ESF may increase in the grassland in the future, but may not in the forest. In general, the ecological restoration in the BTSSCP have improved significantly. Abstract: The Beijing–Tianjin Sandstorm Source Control Project (BTSSCP) has been implemented for more than 20 years (2001–2022), and a scientific, accurate, and complete evaluation of its implementation effect is of great significance for the study of ecosystem evolution. In this study, we present a vegetation–water–soil–environment system comprising the net ecosystem productivity (NEP), water conservation (WC), soil erosion (SE), and habitat quality (HQ) to evaluate the spatiotemporal changes and future trends. The results showed that: (1) In areas with high vegetation coverage, only WC was significantly and negatively correlated with SE (−0.68, p  less than 0.01). In areas with low vegetation coverage, NEP, WC, and HQ were all significantly negatively correlated with SE. This indicates that SE is a basic function that affects the performance of other ecological services. (2) From 2000 to 2020, the annual maximum average vegetation coverage increased by about 10 %; the annual average NEP increased by about 60 g C/km 2, and the annual average SE decreased by about 500 t/km 2 . Compared with Phase I (2000–2010), the vegetation condition (coverage, NEP) in summer (July–August) was improved by about 10 %, and SE in winter (December–January) decreased by 3 t/km 2 per month in Phase II (2010–2020). (3) In terms of future trends, NEP may continue to increase in the grassland area, especially in the Mu Us Sandland, but it may not change significantly in the forest area. Similarly, SE may continue to decrease in grassland-covered areas, but not in forest-covered areas. Most areas of WC could continue to increase, but the HQ will not change significantly. In general, the ecological restoration effects of the BTSSCP have improved significantly. This paper is intended to provide some key information for the management of ecological projects and regional ecological security.